Aquation of impurity distribution in a solid distillate - Kravchenko, A.I. (Functional Materials, 2006)
An equation has been derived describing the distribution of an impurity in a distillate obtained by vapor condensation into solid phase at a low impurity content and under ideal mixing of the substance being distilled.